“Replacing Theological Education with Spiritual Discipline”: Jia Yuming and the Transformation of the Chinese Christian Spiritual Academy - WANG Delong, (Journal of Research for Christianity in China (JRCC), 2025)
The Chinese Christian Spiritual Academy, founded by Jia Yuming in the 1930s, was a localized theological educational institution. Its establishment process and educational philosophy reflected both the faith orientation of Chinese fundamentalist believers and the process of Christian localization in China. The slogan “Replace theological education with spiritual discipline” served to counter the spread of liberal theology in China to some extent, while simultaneously introducing a tendency toward mysticism in the development of Chinese Christianity. As a product of the Chinese fundamentalist movement's localization efforts, the Spiritual Academy advocated equal emphasis on theological education and spiritual cultivation, fostering the symbiosis of knowledge and spiritual practice. It produced a cohort of steadfast Chinese Christian pastors and became a quintessential model of early Christian adaptation to Chinese culture.